Population size estimation of penthetor lucasi in wind cave, Bau, Sarawak - Barapoi, Inu Puun. (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Accurate estimation of population size is essential for understanding the dynamics and structure of natural populations, as well as for assessing conservation status. A study was done in Wind Cave, Bau from October 14th to October 22nd, 2003, to estimate the population size of Penthetor lucasi. Throughout this study, 765 individuals of P. llica i were captured and from these, a total of 27 individuals were recaptured. Due to the nature of sampling methods, it was initially assumed that the population of P. lucasi in Wind Cave, Bau is a closed population. Three closed mark-recapture model estimators were applied in this study, namely the Lincoln-Petersen, the Schnabel, and the Schumacher-Eschmeyer method. The population size of P. lucasi analysed using the Lincoln-Petersen method were rather unrealistic and not convincing as compared to the estimations calculated using the Schnabel, and the Schumacher-Eschmeyer estimators. Determination of the appropriate sample size led to a Coefficient of Variation of ±0.2; only 40 % data were achieved. Further, testing for any violations against a closed population assumptions were also performed. Unfortunately, the closed population assumptions were clearly violated, leading to all closed population estimations as being invalid. The Tanaka model was subsequently computed: an estimated population size of28338 individuals was achieved. In addition, if a 100% data were to be achieved, the popUlation estimation should be 70845 individuals. This estimate will form the basis of our population estimation for P. lucasi in Bau Cave, Sarawak.